Accessibility of Rural Tourism Services for the Disabled in Lithuania - Juodisius M., Uspuriene A. B. (A breakthrough in science: development strategies, 2020)
rural tourism has great potential for attracting people with different interests, but it requires close cooperation in the planning and implementation of strategic development directions and measures related to tourism. At present time, the social model of integration of the disabled is becoming more and more established. A person with a disability needs adapted infrastructure to travel. Actions should be implemented in accordance with the principle that people with disabilities, like all people, need access and integration. Therefore, it is important to study the accessibility of rural tourism services for the disabled in Lithuania.
Keywords: инвалидность; сельский туризм; disabled; rural tourism; доступность услуг; services accessibility